Eksplorasi Hybrid Learning dari Perspektif Guru (Studi Kasus: SMAN 3 Pasuruan) - Selly Aqidatul Izza; Diah Priharsari; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Hybrid Learning is a learning model that combines online and offline learning. Hybrid Learning is expected to be a learning solution during the COVID-19 pandemic because offline learning cannot be eliminated. SMAN 3 Pasuruan applies hybrid learning with a composition of 50% online learning is carried out by providing materials and assignments through Google Classroom and 50% offline learning is carried out offline by dividing 2 sessions per class. Hybrid learning is considered a learning solution in the midst of a pandemic, but it does not rule out the possibility of creating new problems. This study aims to determine the results of hybrid learning exploration from the teacher's perspective, a case study at SMAN 3 Pasuruan Data collection techniques were carried out by semi-structured interviews with 12 teachers of SMAN 3 Pasuruan. Data analysis was carried out using a qualitative coding method, using the help of the QDA Miner Lite application. Data analysis was carried out by using a qualitative coding method, using the help of the QDA Miner Lite application. The results of data analysis found that hybrid learning at SMAN 3 Pasuruan from the teacher's perspective was implemented quite well in terms of the schedule, time, learning media and communication media that went well according to the school's direction when implementing hybrid learning. Other results found that during hybrid learning teachers became innovators because they applied interesting learning models during hybrid learning, and looked for support to help the ease of the implementation of hybrid learning. It was also found the impact during the implementation of hybrid learning such as the decline in student attitude and manners, the improvement of students' creativity, teachers' demotivation, and the piling up of teachers' assignment. The obstacle of the implementation of hybrid learning from the teacher's perspective is the lack of students' facilities.